The immediate results of valve-sparing complete repair of tetralogy of Fallot - I. A. Kozyrev; A. A. Morozov; E. V. Grekhov; I. A. Averkin; M. L. Gordeev; A. K. Latypov (Патология кровообращения и кардиохирургия, 2019)
Aim. The present study aimed to evaluate the immediate results after the primary valve-sparing complete repair of tetralogy of Fallot. Methods. The study included patients with tetralogy of Fallot who were aged <6 months and who underwent primary complete repair between January 2017 and December 2018. According to the surgical approach, the patients were divided into two groups: valve-sparing repair and transannular plasty. Data were obtained from medical records and included echocardiography findings and surgical information. The dimensions of the pulmonary valve were assessed using Z-scores. Results. In total, 38 patients were included in this study. Among these, 25 (66%) patients were included in the valve-sparing repair group. The valve-sparing repair group had lower cardiopulmonary bypass time, epinephrine support duration, and pulmonary valve Z-scores than the transannular plasty group. Additionally, the valve-sparing repair group had a significantly higher postoperative pulmonary valve Z-score than the preoperative score. Conclusion. Valve-sparing complete repair of tetralogy of Fallot is possible in the majority of patients. Pulmonary valve preservation reduces cardiopulmonary bypass time and provides a more stable early postoperative period by reducing the epinephrine support duration. Received 13 March 2019. Revised 24 March 2019. Accepted 8 April 2019. Funding: The study did not have sponsorship. Conflict of interest: Authors declare no conflict of interest.